Veronica Koman’s Tweets During West Papuan Uproar: Transitivity and Ideology Analysis - Fitria Nur Madia; Khumrotun Nadlifah; Lina Purwaning Hartanti (Lakon : Jurnal Kajian Sastra dan Budaya, 2022)
The current study is to emphasize Veronica Koman's perspective and how she became one of the most famous human rights advocates during the November 2019 West Papuan protest. The tweets of Veronica Koman were evaluated using CDA and transitivity analysis. The researchers used observation and documentation to detect processes and other linguistic cues in the documented tweets. Koman used transitivity to tweet about what transpired in West Papua. They said her tweets evoked pictures of the crisis, encouraging people across the country and globally to learn about West Papua. As a social-political journalist, she aimed to guarantee that injustice and bigotry were criticized by the Indonesian people, and pushed them to express their displeasure.